Vulture Scavenging of Pig Remains at Varying Grave Depths - (:unkn) unknown (My University, 2020)
Vulture Scavenging of Pig Remains at Varying Grave DepthsFrom November 2012 to January 2013, four pig carcasses (Sus scrofa) were buried at varying shallow grave depths at the Forensic Anthropology Research Facility at Texas State University–San Marcos. A fifth pig served as a control on the surface. Modification of the graves and surface deposit was recorded through the use of five motion-sensing cameras and daily on-site observation. The research intended to examine how vultures (Coragyps atratus and Cathartes aura) respond to and modify shallow graves of varying depths. Questions that were to be answered included how and when vultures detect graves; disturb the area; remove, disarticulate, and skeletonize remains; and finally abandon the different graves in comparison to a surface deposition. Vultures in this study did not locate or unearth the pig carcasses in the shallow burials and this may be explained by vulture seasonality and migration, feeding behavior regarding digging, and most importantly, the presence of human disturbance.
Keywords: Forensic science; forensic anthropology; physical anthropology; taphonomy; postmortem scavenging; vultures; burials; time since death; decomposition; postmortem interval